Long Distance Transport of Subsurface Sediment‐Derived Iron From Asian to Alaskan Margins in the North Pacific Ocean - M. Sieber; N. T. Lanning; J. M. Steffen; X. Bian; S.‐C. Yang; J. M. Lee; G. Weiss; H. R. Hunt; M. A. Charette; W. S. Moore; S. L. Hautala; M. Hatta; et al. (Geophysical Research Letters)
Abstract The international GEOTRACES program has been instrumental in demonstrating how marine sediments are a critical source of dissolved Fe to the world's oceans. Here, we present dissolved iron (dFe) from the GEOTRACES North Pacific GP15 section, which, alongside other sediment‐source tracers (including dissolved δ56Fe, Mn, 228Ra, and particulate Fe), allows for identification of the dFe provenance of three distinct dFe depth maxima at the Alaskan margin. Two of these (shelf and abyssal depths) are of local Alaskan sedimentary origin. The third, a mid‐depth dFe maximum with an absence of 228Ra, is an advected signal that, based on tracer data from Western Pacific GEOTRACES transects and circulation models, must be advected from sedimentary sources on the Asian margin, ∼5,000 km away. This study illustrates the importance of measuring diagnostic sedimentary tracers like radium when assigning local margins as sedimentary sources of marine trace metal budgets.